Decentralised governance and participatory development : issues, constraints and prospects - Mohanan, B. 1957- (New Delhi : Concept Pub., 2005)
With special reference to Kerala State, India
Includes bibliographical references and index
Keywords: Decentralization in government -- Kerala -- India; Panchayat -- Kerala -- India; Political participation -- Kerala -- India